Litchi is safe and nutritious - Nath, Vishal (Indian Horticulture, 2019)
The queen of fruits, litchi, is being grown and relished since thousands of years in its original ‘habitat’, China. Litchi was introduced in India in 18th century and has been savoured by the locals since then. It is being consumed for about 2000 years while acute encephalitis syndrome (AES) is being reported from Muzaffarpur only and that too since last few years. Various litchi products such as litchi squash, litchi kishmish and litchi nuts are also relished by people round the year. The numerous health benefits and its uses in various traditional Chinese medicine systems along with potential hypoglycaemic effects of litchi seed are documented. However, hypoglycaemia alone may not be able to explain encephalopathy, which usually persists in spite of infusion of glucose as reported. Many AES cases were reported in 2013 and 2014 but despite a very good crop of litchi in 2016 season, very few AES cases as compared to earlier 2 years were reported. Further, AES cases are also reported in April and July months when litchis are not available in Muzaffarpur.